Danish experiences in integrating International Humanitarian Law and International Human Rights Law in capacity building - Kristoffer Nilaus Tarp; Mikkel Runge Olesen (Danish Institute for International Studies (DIIS), 2015)
This paper seeks to document Danish experiences with integrating International Humanitarian Law (IHL) and International Human Rights Laws (IHRL) in capacity building and training of foreign armed forces. It is the first such attempt to present experiences from different international missions and engagements and has thus relied on 'inventing' ways and means of identifying and documenting these. The paper builds on a range of interviews with individuals directly or indirectly involved in training and capacity building activities such as military legal advisors and civilian advisors as well as members of the armed forces. Further, the paper draws on presentations and discussions at a Nordic seminar on IHL and IHRL in capacity building held in Copenhagen on 17 November 2015. The majority of relevant Danish military legal advisors were identified and interviewed for this paper. However, the paper would have benefitted from additional interviews with officers in the armed forces with hands on experience from IHL and IHLR capacity building and training in international missions. Future analysis could therefore focus on further identification of practitioners involved in IHL and IHRL training and capacity building from within the armed forces. While the paper presents an overview of IHL and IHRL capacity building and training activities to date it does not satisfactorily present the impact of these activities. Respondents were all asked about their views on the outcomes of the activities conducted in terms of changed behaviour, procedures and practises. However, due to the ad hoc and often discontinued nature of their work, few offered any views on the impact generated. This paper therefore argues that more should be done to monitor the outcomes and impact of IHL and IHRL capacity building and training including through establishing a baseline i.e. some form of assessment of IHL and IHRL adherence prior to the capacity building and training intervention. At the end of this working paper, key findings have been grouped under 5 thematic categories to provide the reader with 'easy access' to key observations. A list of useful resources on IHL and IHRL, all of which can be accessed online, is also included.
Keywords: 330